The Moderating Role of Ego Depletion in the Relationship between Moral Integrity and Psychological Well-being - Abdul Rahman, Agus; Noviyanti, Dela (Psympathic : Jurnal Ilmiah Psikologi, 2025)
Psychological well-being is influenced by moral and self-regulatory processes, particularly in religious and cultural contexts. This study examined the effects of moral integrity and ego depletion on psychological well-being and tested the moderating role of ego depletion. Using a quantitative correlational design, data were collected from 247 Muslim undergraduate students of Sundanese ethnicity. Moderation analysis using a general linear model indicated that moral integrity positively predicted psychological well-being, whereas ego depletion negatively predicted psychological well-being. Although the interaction effect was relatively small, further analyses using simple slopes and the Johnson-Neyman technique revealed that ego depletion conditioned the strength of the relationship between moral integrity and psychological well-being, with stronger effects observed at higher levels of ego depletion. These findings suggest that moral integrity remains a protective factor for psychological well-being, particularly under conditions of increased self-regulatory demands. The study highlights the importance of considering self-regulatory fatigue when examining the psychological benefits of moral integrity in religious populations.